Joining of carbon steel AISI 1006 to aluminum alloy AA6061-T6 via friction spot joining technique - Ridha, Munaf Hashim; Saad, Mursal Luaibi; Abdullah, Isam Tareq; Barrak, Osamah Sabah; Hussein, Sabah Khammass; Hussein, Abbas Khammas (Zielona Góra: Uniwersytet Zielonogórski)
This work aims to join sheets of carbon steel to aluminum alloy AA6061. A lap joint arrangement was used with a joint lap area of dimensions 25x25 mm. The joining procedure was carried out using a rotating tool of 10 mm shoulder diameter. Three process parameters, with three levels for each parameter, were selected to investigate their effects on joints quality. The parameter`s levels for each experiment were designed using the design of the experiment method (DOE).
Keywords: friction spot; joining; AA6061; carbon steel AISI 1006; DOE